The F-0 exuvia of Protoneura paucinervis Selys, 1886 (Zygoptera: Protoneurinae): description and diagnosis - Ferreira, Eloiza Helena; Vilela, Diogo Silva; Hamada, Neusa (Zootaxa, 2024)
The F-0 exuvia of Protoneura paucinervis Selys, 1886 is described, illustrated, and diagnosed by comparison with the hitherto known Protoneura Selys in Sagra, 1857 larvae. The larvae of P. paucinervis can be distinguished from its congeners by the following combination of characters: palpal lobe squared bearing three strong teeth, 5 palpal setae, and nodus of lateral gills at 0.77 of its length.